An Unusual/Varied Presentation of Two Cases of Tuberculous Meningitis - Meera Praful Shah; Jitendra D. Lakhani; Kinjal Satish Patel; Vivek N. Vaswani (Journal of Integrated Health Sciences)
Tuberculosis (TB) in India has varied presentation which may manifest as pulmonary as well as extrapulmonary disease leading to difficult diagnosis. Here is the presentation of two cases of tuberculous meningitis (TBM). The first case was of a 35-year-old female having cortical paraparesis along with IX and X cranial nerve palsy. Magnetic resonance imaging of the brain with contrast showed multiple ring-enhancing lesions suggestive of TBM. The second case was of a 17-year-old female with anemia, hyponatremia, and hypochloremia having disseminated TB in the lungs, abdomen, and meninges. TBM presentation maybe varied and may present with disseminated TB.